Exploring the Dimensions of Business Performance: A Conceptual Framework for Sustainable Success - Islam , Md Ariful (South Asian Journal of Social Sciences and Humanities, 2024)
In today's volatile and cutthroat business environment, companies must overcome a myriad of  economic, financial, and social challenges in order to provide consumers with exceptional  value. A company's ability to sustain service quality and the elements that contribute to its  improvement is crucial, since businesses in this sector face higher levels of vulnerability and  competition than other sectors. Looking at things from several aspects, this research shows how  company performance and associated issues are viewed from a broad perspective, which has  real-world consequences for everyone involved. The researchers drew on previous research  that had already shown how many creative techniques and aspects affected company success.  Both academics and practitioners can benefit from the study's recommendations and  suggestions.
Keywords: Business Performance; Sustainable Success; Influential Dimensions